Hydrophilic Sugars for Enhancing Dissolution Rate of Cilostazol: Effect of Wet Co-Processing - Alaa Yosf Bazeed; Ahmed Nouh; Ebtessam Ahmed Essa; Gamal El Maghraby (Tabriz University of Medical Sciences, 2021)
Background: Cilostazol is an anti-platelets drug with considerable antithrombotic effects in vivo. Therefore, it is widely used by elderly patients. However, it suffers from poor bioavailability due to its low aqueous solubility. The objective of this work was to enhance the dissolution of cilostazol with the aim of formulating fast dissolving tablets for geriatrics and those of swallowing difficulties. Methods: Ethanol-assisted co-grinding of cilostazol with sugar-based excipients was adopted. Sucralose and mannitol were used for this purpose as hydrophilic excipient as well as taste improving agents. The obtained products were investigated regarding differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction, scanning electron microscope (SEM) and in vitro drug dissolution. Fast disintegrating tablets were prepared and evaluated. Results: Thermal behavior of the developed products reflected reduced crystallinity, it also suggested possible existence of new crystalline species with sucralose. Eutexia was also suggested for mannitol mixtures, that was supported by X-ray diffraction data. SEM indicated size reduction with the deposition of the drug as submicron particles over the excipient surface. Co-processing markedly improved cilostazol dissolution compared to unprocessed drug. The optimized formulations were successively formulated into fast disintegrating tablets. Conclusion: This investigation introduced the wet grinding strategy with sugar excipients as a platform for the formulation of easy to use tablets with optimum drug release.